Sustainable micropollutant bioremediation via stormwater biofiltration system. (1st May 2022) - LeviRam, I.; Gross, A.; Lintern, A.; Henry, R.; Schang, C.; Herzberg, M.; McCarthy, D.
Highlights: Stormwater biofiltration system targeting atrazine removal was developed. Introduction of GAC enhanced proliferation of micropollutant-degrading bacteria. Full atrazine removal was recorded, significantly beyond the GAC adsorption capacity. Kinetics of t rzN gene abundance was accelerated on GAC vs. sand (0.8 vs. 0.37 week −1 ). Consistent removal of other typical stormwater macropollutants. Abstract: Waters contaminated with micropollutants are of environmental and public health concern globally. Stormwater is a significant source of anthropogenic micropollutants to receiving waters. Hence, sustainable stormwater remediation is needed to reduce contamination of waterways. Yet designing sustainable bioremediation solutions, including those targeted to remove micropollutants, is a major scientific challenge. This study aimed to adapt the design of stormwater biofiltration systems, to improve the removal of micropollutants and understand the role of the micropollutant-degrading bacteria in this bioremediation process. We investigated the atrazine removal performance of a prototype biofiltration system, in which the filter media was supplemented with Granulated Activated Carbon (GAC). The prototype biofiltration system completely removed atrazine to below detectable limits, significantly exceeding the GAC's adsorption capacity alone, suggesting other biological processes were present. We showed that atrazine degradation capacity, measured by the kinetics of the trzN gene abundance, was accelerated in the prototype system compared to the standard system (which had no added GAC; 0.8 vs. 0.37 week −1, respectively). Notably, this high level of atrazine removal did not come at the expense of the removal performance of other typical stormwater macropollutants (e.g., nutrients, suspended solids). The prototype biofiltration system showed a proof-of-concept of sustaining microbial remediation of a model micropollutant alongside stormwater macropollutants, which could be used to reduce impacts on receiving waterways and protect our ecosystems and human health. Abstract : Image, graphical abstract .